Determining the Drug-Like Properties of Ailanthone, a Novel Chinese Medicine Monomer with Anti-CRPC Activity - Hu, Pan; Guo, Dandan; Xie, Jiayi; Chen, Huang; Hu, Shixiu; Bian, Aiwu; Xu, Shifen; Yi, Zhengfang; Peng, Shihong; Liu, Mingyao (Planta Medica, 2020)
Approximately 40% of compounds with therapeutic potential cannot be successfully developed into drugs owing to their poor pharmaceutical properties, emphasising the need to profile their drug-like properties as early as possible during preclinical development. This study aimed to evaluate the drug-like properties of ailanthone, a novel Chinese medicine monomer that was shown to have activity against castration-resistant prostate cancer tumour growth and metastasis in our previous study. The drug-like properties detected in the present study included effects on permeability, liver microsome stability, plasma protein binding rate, plasma stability, and human ether-à-go-go-related gene inhibition. Additionally, the following results were obtained: the efflux ratio of ailanthone was > 32 during permeability detection; the half-life and intrinsic clearance (Clint) in mouse, rat, and human liver microsomes were > 145 min and < 9.6 µL/min/mg protein, respectively. The Clint(liver) of ailanthone was < 38.0, < 17.3, and < 8.6 mL/min/kg body weight in mice, rats, and humans, respectively. The plasma protein binding percentage of ailanthone was 16.6 ± 4.2% in human plasma, with 62.5% remaining at 120 min after incubation. The IC50 value of ailanthone for the human ether-à-go-go-related gene channels was > 30 µM. Collectively, these results and those from our previous study indicate that the pharmacokinetic properties of ailanthone are suitable for the potential development of this compound as an oral or intravenous drug for the treatment of castration-resistant prostate cancer.
Keywords: AIL; Simaroubaceae; drug-like properties; LC-MS/MS